Status Characteristics and Ability Attributions in Hungarian School Classes: An Exponential Random Graph Approach. (June 2016) - Grow, André; Takács, Károly; Pál, Judit
We study how the status characteristics gender and ethnicity affect the abilities that adolescents attribute to each other in the Hungarian school context. For this, we derive predictions from status characteristics theory that we test by applying exponential random graph models to data collected among students in 27 school classes. By that, we contribute to the few existing studies of status characteristics in a school context, and we propose a novel approach to handle structural dependencies between individual ability attributions. Our results suggest that across classes, gender does not consistently affect ability attributions, while ethnicity does affect ability attributions. Roma students are on average perceived as less able than their Hungarian peers, even after controlling for the structural embeddedness of these perceptions.